Meningkatkan Daya Saing UMKM Tempe: Inovasi Kemasan dan Edukasi Pemasaran di Desa Dolok Sagala - Titin Elfrida Situmorang; Suwadi Suwadi; Yenni Arfah; Rika Zalukhu; Abednego Ketaren; Nursaimatussaddiya Nursaimatussaddiya; Azril Syahputra; Rahma Yanti Batubara; Putri Andria (Community Service Progress, 2026)
This community service program was conducted in Dolok Sagala Village, Dolok Masihul District, Serdang Bedagai Regency, as part of the Community Service Program (KKN) of STIE Bina Karya Tebing Tinggi. The program focused on the theme "Product and Packaging Innovation to Attract Consumers to MSMEs in Dolok Sagala." The program's primary target was a local tempeh MSME owned by Mrs. Merry and Mr. Jumiran. Methods used included observation, interviews, and direct implementation, including designing and producing new, more attractive product packaging, as well as promotional media such as stickers and banners. The results demonstrated the creation of new packaging aimed at increasing sales value, attractiveness, and consumer trust. In addition to the main MSME program, supporting activities were also implemented, such as anti-bullying outreach in elementary schools and the installation of educational signs on waste management. These activities successfully provided new insights for MSMEs regarding the importance of branding and packaging in increasing product competitiveness.